Haze - Thomas, E. L. (Orca sports, 2012)
Bram's friend Jeremy wants to go public with information about a hazing-related student death. The morning after he tells Bram this, he's injured in a hit-and-run accident. Now Jeremy is in a coma, and Bram is trying to follow the trail that he left. The trouble is, Abby, Jeremy's sister, is convinced Bram's swimming coach is to blame. Bram knows Coach is innocent, but can he prove it? And what will happen if he's wrong?